Antitumor effects of 4‐methylumbelliferone, a hyaluronan synthesis inhibitor, on malignant peripheral nerve sheath tumor. Issue 2 (18th October 2016) - Ikuta, Kunihiro; Ota, Takehiro; Zhuo, Lisheng; Urakawa, Hiroshi; Kozawa, Eiji; Hamada, Shunsuke; Kimata, Koji; Ishiguro, Naoki; Nishida, Yoshihiro
Abstract : Hyaluronan (HA) has been shown to play important roles in the growth, invasion and metastasis of malignant tumors. Our previous study showing that high HA expression in malignant peripheral nerve sheath tumors (MPNST) is predictive of poor patient prognosis, prompted us to speculate that inhibition of HA synthesis in MPNST might suppress the tumorigenicity. The aim of our study was to investigate the antitumor effects of 4‐methylumbelliferone (MU), an HA synthesis inhibitor, on human MPNST cells and tissues. The effects of MU on HA accumulation and tumorigenicity in MPNST cells were analyzed in the presence or absence of MU in an in vitro as well as in vivo xenograft model using human MPNST cell lines, sNF96.2 (primary recurrent) and sNF02.2 (metastatic). MU significantly inhibited cell proliferation, migration and invasion in both MPNST cell lines. HA binding protein (HABP) staining, particle exclusion assay and quantification of HA revealed that MU significantly decreased HA accumulation in the cytoplasms and pericellular matrices in both MPNST cell lines. The expression levels of HA synthase2 (HAS2) and HA synthase3 (HAS3) mRNA were downregulated after treatment with MU. MU induced apoptosis of sNF96.2 cells, but not sNF02.2 cells. MU administration significantly inhibited the tumor growth of sNF96.2 cells in the mouse xenograft model. To the best of our knowledge, our study demonstrates for the first time the antitumor effects of MU on human MPNST mediated by inhibition of HA synthesis. Our results suggest that MU may be a promising agent with novel antitumor mechanisms for MPNST. Abstract : What's new? A novel therapeutic tool is needed to improve prognosis in patients with malignant peripheral nerve sheath tumors (MPNSTs), rare and highly aggressive tumors that frequently spread despite surgical resection. Poor prognosis in MPNST is predicted by elevated expression of hyaluronan (HA). Here, HA levels were successfully suppressed by the inhibitor 4‐methylumbelliferone (MU), which induced apoptosis in primary recurrent human MPSNT cells and inhibited tumor growth in a xenograft mouse model. Approved clinically as a choleretic and biliary antispasmodic agent and well‐tolerated, MU is an appealing drug with novel antitumor mechanisms for MPNST.